(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2025)
The influence of plastic and its presence in society and ecosystems is so significant that the current era in which we live has been referred to as “the era of plastic,” or, as some authors call it, the Plasticene. Its large-scale commercialization dates back to the second half of the last century, and over time, its production and use have increased, reaching an estimated 367 million tons in 2020. However, recycling rates are very low, and the lack of regulations—or, in the best case, their poor enforcement—has led to plastic being considered an emerging pollutant, drawing the attention of the scientific community. The incineration of plastics generates air pollution and increases the concentration of greenhouse gases. It has been proposed that by 2050, plastics could emit 56 billion tons of greenhouse gas emissions, accounting for as much as 14% of the Earth’s remaining carbon budget. Microplastics and nanoplastics enter various forms of life, affecting all ecosystems, and they also serve as transport vehicles for other pollutants. Agriculture, and particularly the horticultural industry, has become a major consumer of plastics in different forms, which are used in all phases of cultivation, reaching a consumption of 2,250,000 tons per year. Due to the rapid increase in plastic pollution across different environmental matrices, it will be necessary, in the near future, to develop proposals based on technologies for reducing plastic materials in various productive sectors. The goal is to foster a cultural shift among consumers toward generating change and revolutionizing the concept of "Reduce, Reuse, Recycle to one of "Reject, Adapt, and Demand.